Mesothelioma incidence surveillance systems and claims for workers' compensation. Epidemiological evidence and prospects for an integrated framework - Marinaccio Alessandro; Scarselli Alberto; Merler Enzo; Iavicoli Sergio (BMC, 2012)
Abstract Background Malignant mesothelioma is an aggressive and lethal tumour strongly associated with exposure to asbestos (mainly occupational). In Italy a large proportion of workers are protected from occupational diseases by public insurance and an epidemiological surveillance system for incident mesothelioma cases. Methods We set up an individual linkage between the Italian national mesothelioma register (ReNaM) and the Italian workers' compensation authority (INAIL) archives. Logistic regression models were used to identify and test explanatory variables. Results We extracted 3270 mesothelioma cases with occupational origins from the ReNaM, matching them with 1625 subjects in INAIL (49.7%); 91.2% (1,482) of the claims received compensation. The risk of not seeking compensation is significantly higher for women and the elderly. Claims have increased significantly in recent years and there is a clear geographical gradient (northern and more developed regions having higher claims rates). The highest rates of compensation claims were after work known to involve asbestos. Conclusions Our data illustrate the importance of documentation and dissemination of all asbestos exposure modalities. Strategies focused on structural and systematic interaction between epidemiological surveillance and insurance systems are needed.